Togo : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper investigates state-owned financial institutions' (SOFIs) performance in developing economies. It focuses on Sub-Saharan Africa, zooming in on the Togolese experience with SOFIs and privatization, at a time when the Togolese government has decided to further disengage from the financial sector. Typically set up with a public interest and financial inclusion mandate, SOFIs tend to weaken financial stability and fiscal discipline in developing economies, especially if they are not typically regulated and supervised on the same basis as other banks. Togo's and cross-country experiences suggest that performance improves more after privatization when the government fully relinquishes control, when banks are privatized to strategic investors rather than through share issues, and when bidding is open to all, including foreign banks. The success of privatization also hinges on the business environment for competition, governance, and entry, on banks' valuation and how policy concerns are dealt with, as well as on owner's prudential review quality.